Ecclesia Reformata in the Digital Era: Calvin on Worship and the Online Church - Bobby Kurnia Putrawan; Annie George (Journal of Religious and Socio-Cultural, 2025)
The COVID-19 pandemic and rapid technological advancement have reshaped how churches conduct worship, pushing many congregations toward online platforms. This shift has raised critical theological questions, especially within the Reformed tradition, regarding the authenticity and integrity of digital worship. John Calvin’s theology of worship, which emphasizes God’s presence, the centrality of Scripture, and the communal nature of the church, provides a valuable framework for evaluating these changes. This article aims to examine how Calvin’s theological principles can be applied to online worship. It seeks to explore whether digital worship can remain theologically coherent within a Reformed framework and how churches can adapt Calvin’s insights for contemporary contexts. Using a theological-literary approach, this study analyzes Calvin’s writings on worship—particularly his views on Scripture, prayer, sacraments, and the gathered community—and compares them with the practices and challenges of online worship. Scholarly perspectives on digital religion are also engaged to assess the ongoing debate. The study finds that while online worship cannot fully replace the richness of physical gatherings—especially in relation to the sacraments—it can still nurture genuine spiritual experiences. If grounded in Scripture, focused on God’s presence, and supported by intentional practices of fellowship, online worship may uphold Reformed theological integrity. However, it requires careful pastoral oversight to avoid doctrinal dilution and to maintain the centrality of Word and prayer.